Effect of Pre-sowing Treatments on Vegetative Growth and Production of Graftable Rootstocks in Mango - Banyal, Sanjeev Kumar; Shivandu, Shiv Kumar; Patial, Uday Raj (International Journal of Bio-resource and Stress Management, 2021)
The present investigations “Studies on the effect of pre-sowing treatment and time of wedge grafting on production of saleable grafts in mango”were carried out in the nursery block of Fruit Science Department. The study was conducted using wild mangoes seeds. The seeds were divided in two equal halves, one half of seeds were sown with intact seed coat (K1) while, in other half the mango kernels were extracted (K2), both type of seeds were then soaked in 6 different chemicals of varying concentrations viz. C1- KNO3 @ 0.5%, C2- KNO3 @ 1%, C3- KNO3 @ 1.5%, C4- BA @ 50 ppm, C5- BA @ 100 ppm, C6- GA3 @ 100 ppm, C7- GA3 @ 200 ppm, C8- beejaaumrit @ 2%, C9- beejaaumrit @ 3%, C10- panchgavya @ 2%, C11- panchgavya @ 3% for 12 hours and C12- Control. The germination and vegetative parameters were observed. The results of study revealed that the e×tracted kernels pre-soaked with GA3 @ 100 ppm produced earliest germination, 50 % germination, high rate of germination, germination percentage, number of leaves, maximum leaf area, highest seedling vigour index, while, on pre-soaking extracted kernel with KNO3 @ 0.5% produced maximum seedling diameter. The Seedling raised from extracted kernels pre-soaked in KNO3 @ 0.5% (C1K2) attained graftable diameter within 210 days of sowing. The present investigation was conducted during 2019-2020 at the nursery block of College of Horticulture and Forestry, Neri Hamirpur (H.P) to study the effect of pre-sowing treatments on germination, growth and production of graft-able seedlings.